2020
DOI: 10.1016/j.eclinm.2020.100575
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of olfactory dysfunction accurately detects asymptomatic COVID-19 carriers

Abstract: Background COVID-19 threatens the global community because a large fraction of infected people are asymptomatic, yet can effectively transmit SARS-CoV-2. Finding and isolating these silent carriers is a crucial step in confining the spread of the disease. A sudden loss of the sense of smell has been self-reported by COVID-19 patients across different countries, consistent with expression of the molecular factors mediating SARS-CoV-2 uptake into human olfactory epithelial supporting cells. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 52 publications
1
64
1
Order By: Relevance
“…The olfactory signaling pathway is associated with 18/19 clinical manifestation groups from the GWAS results. This pathway involves enzymatic activity that initiates the binding of an odorant molecule to a receptor resulting in an electrical signal that is transmitted to the brain(23). The olfactory signaling pathway was the top pathway for the asthma exacerbation, hematologic, respiratory failure, and gastrointestinal GWAS clinical manifestations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The olfactory signaling pathway is associated with 18/19 clinical manifestation groups from the GWAS results. This pathway involves enzymatic activity that initiates the binding of an odorant molecule to a receptor resulting in an electrical signal that is transmitted to the brain(23). The olfactory signaling pathway was the top pathway for the asthma exacerbation, hematologic, respiratory failure, and gastrointestinal GWAS clinical manifestations.…”
Section: Resultsmentioning
confidence: 99%
“…The olfactory signaling pathway was the top pathway for the asthma exacerbation, hematologic, respiratory failure, and gastrointestinal GWAS clinical manifestations. There is clinical evidence that some individuals infected with SARS-CoV-2 experience a loss of smell and taste(23). Furthermore, it has been found that olfactory receptors may be an alternative SARS-CoV-2 entry into the local host cells, which may lead to its spread into the central nervous system(24).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, our findings support the idea that SCENTinel 1.0 represents a rapid, accurate, flexible, and cost-effective tool to deploy a smell test on large scale population surveillance efforts. The development of SCENTinel 1.0 has been spurred by the new sudden loss of smell that characterizes COVID-19, including among nominally asymptomatic individuals, many of whom had smell loss but were not aware of before receiving an objective olfactory test (Gözen et al, 2020;Bhattacharjee et al, 2020) . Yet, the large-scale availability of a validated rapid smell test can benefit not only health emergencies such as COVID-19, but also be used in early detection and monitoring of a variety of clinical conditions, including psychiatric, neurological and neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory impairment is a common manifestation of COVID-19, with meta-analyses indicating a prevalence of 77-86% in studies using standardized olfactory testing [8][9][10][11]. Among patients with COVID-19 assessed for smell loss, 41% and 98% had impaired tests of olfaction on two different tests of olfactory function [12,13], suggesting that smell loss may aid in COVID-19 case identification [14].…”
Section: Introductionmentioning
confidence: 99%